Interaction between cells in dielectrophoresis and electrorotation experiments - Sancho, Miguel (American Institute of Physics, 2010)
Progress in microelectrode-based technologies has facilitated the development of sophisticated methods for manipulating and separating cells, bacteria, and other bioparticles. For many of these various applications, the theoretical modeling of the electrical response of compartmentalized particles to an external field is important. In this paper we address the analysis of the interaction between cells immersed in rf fields. We use an integral formulation of the problem derived from a consideration of the charge densities induced at the interfaces of the particle compartments. The numerical solution by a boundary element technique allows characterization of their dielectric properties. Experimental validation of this theoretical model is obtained by investigating two effects: (1) The influence that dipolar “pearl chaining” has on the dielectrophoretic behavior of human T lymphocytes and (2) the frequency variation of the spin and orbital torques of approaching insulinoma β-cells in a rotating field.